Analysis of Postoperative Recurrence in Stage I–III Midgut Neuroendocrine Tumors. (26th September 2017) - Cives, Mauro; Anaya, Daniel A.; Soares, Heloisa; Coppola, Domenico; Strosberg, Jonathan
Abstract: Background: Surgery represents the only curative treatment for stage I–III midgut neuroendocrine tumors (NETs). At present, there are very limited data on the risk of postoperative recurrence. The optimal modality, duration and frequency of surveillance have not been well established. In this work, we investigated the long-term risk of recurrence, peak timing of recurrence, and potential predictors of relapse in patients with stage I–III midgut NETs. Methods: We retrospectively evaluated 129 patients with stage I–III midgut NETs who were seen at the Moffitt Cancer Center between 2000 and 2010 following an R0/R1 resection. Disease-free survival (DFS) was estimated using the Kaplan-Meier method. Demographic, clinical, and pathological features were assessed as potential predictors of recurrence. All statistical tests were two-sided. Results: After a median postoperative follow-up of 81 months (range = 1–295 months), recurrence was diagnosed in 40 out of 129 patients (31.0%, 95% confidence interval [CI] = 23.0% to 39.0%). Liver, mesentery, and pelvic lymph nodes were the main sites of relapse. The median DFS was 138 months (95% CI = 117 to 223 months). Resection of 17 or fewer lymph nodes predicted relapse ( P =  .01) and shorter DFS ( P =  .04). Among patients who relapsed, the cumulative risks of recurrence at one, five, and 10 years were 15.0% (95% CI = 3.9% to 26.1%), 50.0% (95% CI = 34.5% to 65.5%), and 85.0% (95% CI = 73.9% to 96.0%). No recurrence was observed among patients (n = 6) with stage I tumors, whereas similar rates of relapse were noted in patients with stage II or III NETs (n = 118). Conclusions: An annual surveillance interval may allow early detection of recurrence. Given the apparent decline in recurrence after eight years from surgery, a decade-long duration of active surveillance may be proposed.